2007
DOI: 10.1007/s00468-007-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vessel size, vessel density and xylem conducting efficiency within a crown of silver birch (Betula pendula)

Abstract: Spatial patterns in vessel diameter, vessel density and xylem conducting efficiency within a crown were examined in closed-canopy trees of silver birch (Betula pendula). The variation in anatomical and hydraulic characteristics of branches was considered from three perspectives: vertically within a crown (lower, middle and upper crown), radially along main branches (proximal, middle and distal part), and with respect to branch orders (first-, second-and third-order branches). Hydraulically weighted mean diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 65 publications
2
35
3
7
Order By: Relevance
“…Scaling of conduit diameter with distance from the apex was observed inside the branches and stem when a defined growth ring was followed. Similar results regarding various species have been shown before (Sanio according to Bailey and Shepard 1915;Zimmermann 1978a;Tyree and Zimmermann 2002;Anfodillo et al 2006;Coomes et al 2007;Sellin et al 2008). However, scaling was negligible in the stem compared to more distal crown parts and steeper in B. pendula compared to the conifers (see also Mencuccini et al 2007).…”
Section: Linking Hydraulic Architecture With Crown Architecturesupporting
confidence: 89%
See 3 more Smart Citations
“…Scaling of conduit diameter with distance from the apex was observed inside the branches and stem when a defined growth ring was followed. Similar results regarding various species have been shown before (Sanio according to Bailey and Shepard 1915;Zimmermann 1978a;Tyree and Zimmermann 2002;Anfodillo et al 2006;Coomes et al 2007;Sellin et al 2008). However, scaling was negligible in the stem compared to more distal crown parts and steeper in B. pendula compared to the conifers (see also Mencuccini et al 2007).…”
Section: Linking Hydraulic Architecture With Crown Architecturesupporting
confidence: 89%
“…Conduit frequency was also lower in the lateral branches of the conifers compared to the main branches, but no difference was found in B. pendula. Earlier studies on deciduous species have shown a decrease in conduit diameter and an increase in conduit frequency from the main to the lateral branches (Atala and Lusk 2008;Nygren and Pallardy 2008;Sellin et al 2008). Suggested biological mechanisms behind the acropetal decrease in cell size are distance from the auxin source (Aloni 1987;2001) and the turgor pressure gradient as turgor pressure decreases with increasing tree height leading to reduced cell expansion (Koch et al 2004;Woodruff and Meinzer 2011).…”
Section: Linking Hydraulic Architecture With Crown Architecturementioning
confidence: 97%
See 2 more Smart Citations
“…As trees consume large amounts of water, they have to develop mechanisms for protection against disturbance of their water balance whereas they should be able to restore the water pathway. Both the diameter and the density of vessels directly influence conductivity (Christensen-Dalsgaard, Fournier, Ennos, & Barfod, 2007;Sellin, Rohejarv, & Rahi, 2008).…”
Section: Introductionmentioning
confidence: 99%